IMPACT OF MACRO ECONOMICS VARIABLES ON STOCK PRICES IN SRI LANKAN ECONOMY - Mayadunne, MKMU. (IJRDO - Journal of Business Management, 2017)
This study examines critically the long-run macroeconomic determinants of stock market performance in Sri Lanka between 1996 and 2011. The properties of the time series variables are examined using the Augmented Dickey-Fuller unit root test and most of the incorporated variables in the study were found to have a unit root at level. The Johansen Cointegration test and Ordinary Least Square test results revealed that the stock market performance in Sri Lanka is mainly determined by macroeconomic forces in the long-run. However, the empirical analysis showed that the Colombo Stock Exchange all share price index is more responsive to changes in Real Gross Domestic Product, inflation rate, Interest Rate, Exchange Rate, and Broad Money Supply. While, the entire incorporated macroeconomic variables were found to have simultaneous and significant impact on the Sri Lankan capital market performance in the long-run. The study recommended that investors should pay close attention to Real Gross Domestic Product, inflation rate, Interest Rate, Exchange Rate, and Broad Money Supply in the longrun in their investment decision.